Terpilihnya Zohran Kwame Mamdani Muslim Pertama sebagai Walikota New York - Rakha Pratama Putra; Nazwa Anindita Putri; Putri Ramadhani Bugis; Hendra Maujana Saragih (Himmah: Jurnal Kajian Islam Kontemporer, 2025)
The election of Zohran Kwame Mamdani as Mayor of New York City is an important contemporary political phenomenon in the study of international relations, especially in the context of global cities. New York as a center of world finance, international migration, and global institutions makes its local political dynamics have far-reaching international implications. This paper discusses this phenomenon by placing it within the framework of the relationship between local politics and global economic structures. The main problem in this study is how Mamdani's victory can be understood as a local political response to the structural pressures of the neoliberal global economy, as well as how it affects the role of global cities as sub-state actors in the international system. To answer these problems, this study uses the theoretical framework of International Political Economy, neoliberalism theory, the concept of global cities, and the approach of sub-state actors in International Politics. The methodology used is a qualitative approach through literature studies of academic books, scientific journals, and relevant documents. Key findings show that Mamdani's victory represents resistance to global economic inequality, the strengthening of progressive politics in urban spaces, and the increasing capacity of global cities as normative agents in international politics. In conclusion, political changes at the global city level have significant implications for contemporary international economic and political dynamics. Keywords: Zohran Mamdani, International Political Economy, Global Cities